2017
DOI: 10.5194/tc-2017-182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of short-term variability of meteorological variables on soil temperature in permafrost regions

Abstract: Abstract. Effects of the short-term temporal variability of meteorological variables on soil temperature in northern high latitude regions have been investigated. For this, a process-oriented land surface model has been driven using an artificially manipulated climate dataset. Climate variability mainly impacts snow depth, and the thermal diffusivity of lichens and bryophytes. This latter effect is of opposite direction in summer and winter in most regions. These impacts of climate variability 5 on insulating … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In this study we use a version of the land surface scheme JSBACH 22,36,37 that has recently been advanced by several processes which are particularly important in cold regions, including coupling of soil hydrology and vertical heat conduction via latent heat of fusion 20 and the effects of ice and water content on soil thermal properties 20 , as well as a new dynamic snow model for soil insulation 21,25 . The version used here in particular also includes a dynamic biogeochemical model of lichens and bryophytes 21 which simulates both the extent of lichens and bryophytes and their impact on the vertical heat conduction 21,25 . In total, five snow layers, one bryophyte/lichens layer, and seven soil layers are used in an implicit numerical scheme to solve the heat conduction equation with phase change 21,23 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study we use a version of the land surface scheme JSBACH 22,36,37 that has recently been advanced by several processes which are particularly important in cold regions, including coupling of soil hydrology and vertical heat conduction via latent heat of fusion 20 and the effects of ice and water content on soil thermal properties 20 , as well as a new dynamic snow model for soil insulation 21,25 . The version used here in particular also includes a dynamic biogeochemical model of lichens and bryophytes 21 which simulates both the extent of lichens and bryophytes and their impact on the vertical heat conduction 21,25 . In total, five snow layers, one bryophyte/lichens layer, and seven soil layers are used in an implicit numerical scheme to solve the heat conduction equation with phase change 21,23 .…”
Section: Methodsmentioning
confidence: 99%
“…20,21,25 . This model version has been intensively evaluated in terms of cold regions physical processes at site level and pan-Arctic scale 20,21,24,25 . Additional evaluation plots can be found in the supplemental information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shati et al [17] studied the relationship among soil temperature (at depth of 5 cm) and snow depth, air temperature (at 2 m above the surface), and their results showed that there was a time-dependent, non-linear relationship between soil temperature (at depth of 5 cm) and air temperature (at 2 m above the surface) and the snow cover played a crucial role in the relationship. Beer et al [18] studied the permafrost in the northern hemisphere, and based on meteorological data, the addition of external conditions, such as surface vegetation and snow coverage, was shown to improve the simulation and prediction accuracy of soil temperature changes in frozen-thawed soils. Michalska et al [19] considered that the daily variation of soil temperature in shallow layers showed a continuously fluctuating trend, with good correlation with daily total solar radiation.…”
Section: Introductionmentioning
confidence: 99%